CSF levels of a set of neurotrophic factors (brain-derived neurotrophic factor, nerve growth factor) and neuropeptides (neuropeptide Y, galanin) in epileptic children. (June 2020) - Tekgul, Hasan; Serin, Hepsen Mine; Simsek, Erdem; Kanmaz, Seda; Gazeteci, Hande; Azarsiz, Elif; Ozgur, Su; Yilmaz, Sanem; Aktan, Gul; Gokben, Sarenur
Highlights: Certain neurotrophic factors and neuropeptides have been implicated for the pathogenesis of epileptogenesis. Significantly increased CSF galanin levels were measured in epileptic children with status epilepticus. Profoundly depressed CSF levels of galanin were measured in infants with epileptic encephalopathy. Abstract: This paper aims to investigate the possible roles of a set of neurotrophic factors ( brain-derived neurotrophic factor-BDNF, nerve growth factor-NGF ) and neuropeptides ( neuropeptide Y-NPY, and galanin ) in children with active epileptogenesis. The cerebrospinal fluid (CSF) levels of BDNF, NPY, NGF and galanin were measured with enzyme-linked immunosorbent assays in epileptic children (n = 73) and controls (n = 64). There were no significant alterations in the CSF levels of BDNF, NPY and NGF in epileptic children with active clinical seizures compared with the levels of controls. However profoundly depressed galanin levels were found in infants with epileptic encephalopathy ( mean ± SD:0.63 ± 0.19 pg/ml ) and significantly increased galanin levels were measured in children with drug resistant epilepsy during the period of status epilepticus ( mean ± SD: 6.92 ± 1.19, pg/ml pg/ml ) compared with the levels of controls. Depressed levels of galanin might reflect a defective anti-epileptogenic effect of galanin in infants with epileptic encephalopathy. On the contrary, increased CSF levels of galanin might be a result of anti-epileptogenic effects of this peptide in epileptic children with status epilepticus.